2015
DOI: 10.1007/s00120-015-3809-0
|View full text |Cite
|
Sign up to set email alerts
|

Primär renales Angiosarkom

Abstract: This article reports a case of primary renal angiosarcoma, a very rare and aggressive malignancy, in a 59-year-old male patient. The mean overall survival time is limited to a few months if the diagnosis is made when clinical symptoms are present but chances of a cure can be increased with surgical resection of smaller incidental findings. Due to the lack of a standard therapy, systemic treatment is based on the therapy of other soft tissue sarcomas. The role of adjuvant medical treatment particularly in angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Because of the absence of standard chemotherapy agents intended for PRA, a large variety of chemical substances have been administered. Paclitaxel-based chemotherapy, doxorubicin and the combination of ifosfamide with epirubicin, doxorubicin or anthracycline have been reported (2,5,(52)(53)(54)(55). One study reported the use of oxaliplatin with paclitaxel followed by bevacizumab, but unfortunately patients did not respond (34).…”
Section: Therapeutic Managementmentioning
confidence: 99%
“…Because of the absence of standard chemotherapy agents intended for PRA, a large variety of chemical substances have been administered. Paclitaxel-based chemotherapy, doxorubicin and the combination of ifosfamide with epirubicin, doxorubicin or anthracycline have been reported (2,5,(52)(53)(54)(55). One study reported the use of oxaliplatin with paclitaxel followed by bevacizumab, but unfortunately patients did not respond (34).…”
Section: Therapeutic Managementmentioning
confidence: 99%